Constructing the 'Self' in Islamic Psychology: Challenges and Opportunities - Fachrunisa, Rahma Ayuningtyas (Universitas Muhammadiyah Surakarta, 2024)
The Self is one of the core concepts in Islamic psychology. However, the concept of the Self found in recent Islamic psychology discourse is still quite unclear since its understanding of the soul remains debatable. A deeper study on the concept of the Self should be carried out to refine the essence of the Self in Islamic psychology and straighten the problematic and reductive understanding on these issues. This paper will give brief review on the studies of the Self in Islamic psychology, then provide some views about the challenges and opportunities to develop this concept. Further discussions about this issue are also discussed in this article.